Feline Hypertrophic Cardiomyopathy: The Consequence of Cardiomyocyte-Initiated and Macrophage-Driven Remodeling Processes?. Issue 4 (July 2019) - Kitz, Sarah; Fonfara, Sonja; Hahn, Shelley; Hetzel, Udo; Kipar, Anja
VHypertrophic cardiomyopathy (HCM) is the most commonly diagnosed cardiac disease in cats. The complex pathophysiology of HCM is still far from clear, but myocardial remodeling is a key process, and cardiomyocyte disarray, interstitial fibrosis, leukocyte infiltration, and vascular dysplasia are described histopathologic features. The present study systematically investigated the pathological processes in HCM, with the aim to shed more light on its pathogenesis. Hearts from 18 HCM cases and 18 cats without cardiac disease (controls) were examined, using light and transmission electron microscopy, immunohistochemistry, and morphometric approaches to identify and quantify the morphological changes. Reverse transcription–quantitative polymerase chain reaction was applied to provide additional mechanistic data on remodeling processes. In HCM, the left and right ventricular free wall and septal myocardium exhibited a significantly reduced overall cellularity, accompanied by a significant increase in interstitial Iba1-positive cells with macrophage morphology. In addition, the myocardium of almost half of the diseased hearts exhibited areas where cardiomyocytes were replaced by cell-rich fibrous tissue with abundant small and medium-sized vessels. HCM hearts also showed significantly higher transcription levels for several inflammatory and profibrotic mediators. Our findings suggest that HCM is the consequence of cardiac remodeling processes that are the result of cardiomyocyte damage and to which macrophages contribute by maintaining an inflammatory and profibrotic environment.